TEKNOLOGI PENGOLAHAN DAN PEMANFAATAN KARBON AKTIF UNTUK INDUSTRI - Effendi Arsad; Saibatul Hamdi (Jurnal Riset Industri Hasil Hutan, 2010)
The  activated carbon is very important  for has  processed product activated carbon.   In south Kalimantan has a big prospects due to the big potential of the raw material provided by the nature and industrial waste. There are a lot of raw materials that can be used for the manufacture of activated carbon such as  agricultural waste, sugarcane waste, waste of sawn timber, lives stock waste and coal  processing waste.Manufacture of activated carbon can be done in  ways: chemical  and physical processes. Activation  is very important in the manufacture of activated carbon in addition to the raw materials used. Activated carbon is charcoal that has undergone changes in chemical properties  and physical properties due to be activated with the activator chemical materials or can by heating at high temperatures, so that absorption , surface area, and the ability to absorb become as very good. Activated carbon is used as an absorbent to absorb heavy metals, in medicine and food, on liquor, petroleum chemical, shrimp farming, the sugar industry of gas purification, catalyst and fertilizer processing.Key wood :  technology  processed, activated carbon